Suppressing molecular vibrations in organic semiconductors by inducing strain - Takayoshi Kubo (Nature Portfolio, 2016)
The mobility of organic semiconductors can be tuned by modifying their chemical composition or crystalline properties. Here, the authors show that bending organic single crystals increases their field effect transistor mobility due to restrained molecular vibrations and subsequently reduced dynamic disorder.